Identification and Verification of SLC27A1, PTBP1 and EIF5A With Significantly Altered Expression in Aggressive Pituitary Adenomas - Cheng, Jianhua; Sun, Ruya; Nie, Ding; Li, Bin; Gui, Song Bai; Li, Chu Zhong; Zhang, Ya Zhuo; Zhao, Peng (Frontiers in Surgery, 2022)
Background: Aggressive pituitary adenoma encircling the internal carotid artery has a poor clinical prognosis because of a high surgical risk and a high recurrence rate. This seriously affects patients’ quality of life and yet there is no effective medical treatment. The European Diagnostic Guidelines have recommended the use of temozolomide (TMZ) for these aggressive pituitary adenomas, but the treatment remission rate has been less than 50%. Methods: In this study, transcriptome sequencing of pituitary tumour tissues and TMZ-treated pituitary tumour cell lines were employed to explore the significance gene expressions affecting the efficacy of TMZ treatment for pituitary tumours. To clarify the roles of these gene expressions, six adult patients with pituitary adenomas treated in Tiantan Hospital from 2015 to 2020 and a pituitary adenoma cell line (Att20 sensitive to TMZ treatment) were analyzed by mRNA transcriptome sequencing. The differentially expressed genes were assayed by analyzing the sequencing results, and the expression level of these genes was further verified by immunohistochemistry. In addition, Ki67, VEGF, and p53 of the tumour tissues were also verified by immunohistochemistry. Results: In tumour tissues, mRNA sequencing showed that PTBP1 and EIF5A were significantly overexpressed in primary pituitary adenomas and SLC27A1 was significantly overexpressed in aggressive pituitary adenomas. Also in the pituitary adenoma cell line (AtT20), SLC27A1 expression levels were suppressed by TMZ treatment. Subsequent immunohistochemistry confirmed the sequencing results. Conclusion: High expression of SLC27A1 and low expression of EIF5A and PTBP1 may be potential indicators to predict the progression of aggressive pituitary adenomas, and patients with high SLC27A1 subtype may be sensitive to TMZ in clinical treatments.